SOSIALISASI PEMBERDAYAAN IBU MENUJU JATIWARNA INNOVATORS PERSALINAN POSITIF - Jannah, Roikhatul; Sariana, Erna; Primasari, Nina (IFI cabang Kota Bekasi, 2024)
One way in which the level of reproductive health in society can be measured is through the Maternal Mortality Rate (MMR). Health during pregnancy is one of the efforts that can be improved so that mothers can go through pregnancy and childbirth healthily. One of the sections of society that has the potential to be closest to the health of pregnant women outside of family members is the posyandu cadres. Based on these considerations, this community service program was developed. The initial effort that can be made is to provide outreach to cadres and pregnant women as positive birth innovators. Objective: To socialize the activities of the Mitra Village Development Program in the form of empowering cadres towards Jatiwarna as positive birth innovators in Jatiwarna Village, Pondok Melati District, Bekasi City in 2023. Method: This program carries out several activities including: delivery of material and introduction to pregnancy exercise. Activities are carried out on the day Saturday 20 May 2023 via offline, at Posyandu Huma Akasia RW 08 Jatiwarna Village, Pondok Melati District, Bekasi City. Results: The activity was attended by 51 pregnant women, 25 posyandu cadres from 11 RWs in the Jatiwarna sub-district. This socialization brought the topic